Influence of forage-to-concentrate ratio on the effects of a radiata pine bark extract on methane production and fermentation using the rumen simulation technique - N. Vera; S. Suescun-Ospina; C. Gutiérrez-Gómez; P. Williams; C. Fuentealba; R. Allende; J. Ávila-Stagno (Animal)
Climate change and food safety standards have intensified research into plant-based compounds as alternatives to dietary supplements in animal feed. These compounds can reduce enteric methane (CH4) emissions and the formation of ruminal ammonia. This study investigated the effects of radiata pine bark extract (PBE) supplementation on CH4 production, ruminal fermentation parameters, and nutrient disappearance using the rumen simulation technique in diets with different forage-to-concentrate (F:C) ratios. The experimental design was a 22 factorial arrangement of two F:C ratios [70:30 (HF) vs 30:70 (HC)], without or with PBE (2% on a DM basis). Two consecutive incubations were conducted during 15 days, with 10 days of adaptation, followed by 5 days of sampling. Use of PBE decreased ammonia nitrogen (NH3-N, P < 0.001) and total volatile fatty acids (VFAs, P = 0.019) concentrations, while it increased acetate (P < 0.001) and propionate (P < 0.001) proportions in both diets. However, CH4 yield [mg/g organic matter (OM) disappeared] tended to be reduced by 33.6% (P = 0.088) only in the HF diet supplemented with PBE. The OM disappearance tended to increase (P = 0.079) with PBE; hemicellulose disappearance increased in HF and decreased in HC diets (P < 0.001), whereas protein disappearance decreased in HF and increased in HC diets (P < 0.001). In conclusion, PBE supplementation reduced NH3-N and VFA concentrations in HF and HC diets, but CH4 yield (mg/g OM disappeared) was only reduced in the HF diet. Additionally, nutrient disappearance was dependent on the F:C ratio of the diet, without adverse effects on ruminal fermentation. Hence, the incorporation of radiata PBE into HF diets could serve as an environmentally friendly additive, potentially offering an alternative use for a forestry industry by-product, while beneficially modulating ruminal fermentation.